2018
DOI: 10.1108/jpbm-08-2017-1555
|View full text |Cite
|
Sign up to set email alerts
|

Parent brands’ influence on co-brand’s perception: a model-based approach

Abstract: Purpose This paper aims to investigate what influence the perceptions of two parent brands have on the perception of a newly formed co-brand. Furthermore, it elaborates whether respondents’ evaluations of the parent brands, their familiarity towards the parent brands and their usage of the parent brands affect this influence. Design/methodology/approach Building on both cognitive consistency and information integration theory, this paper proposes a model-based approach to quantify the parent brands’ influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
2
6
1
Order By: Relevance
“…Branding has been a core topic in marketing for decades (Böger et al , 2018), with the belief that a strong brand can lead to a competitive advantage (Keller, 2001). There are three key dimensions of a company’s brand portfolio strategy that impact competitive advantage: scope (i.e.…”
Section: Measurement and Scaling Methodologiesmentioning
confidence: 99%
“…Branding has been a core topic in marketing for decades (Böger et al , 2018), with the belief that a strong brand can lead to a competitive advantage (Keller, 2001). There are three key dimensions of a company’s brand portfolio strategy that impact competitive advantage: scope (i.e.…”
Section: Measurement and Scaling Methodologiesmentioning
confidence: 99%
“…In the FMCG sector, packaging is often the most effective way to build uniqueness (Anselmsson et al , 2007; Mao et al , 2023). Because uniqueness and quality are ultimately perceptions created by the brand attributes and concretized as perceptions and associations in the consumer’s mind (Anselmsson et al , 2007; Böger et al , 2018; Erdem et al , 2004; Hudders, 2012), they can be seen as concretizing in the interaction between the brand and the consumer and can be affected by brand elements and the consumer’s thoughts. Figure 1 locates uniqueness and quality between the PL brand architecture and the premium PL brand image using double-headed arrows.…”
Section: A Conceptual Framework For the Emergence Of A Values-based P...mentioning
confidence: 99%
“…Researchers have revealed that consumer perceptions of different brands in PL brand portfolios influence each other (Böger et al , 2018; Geyskens et al , 2010; Palmeira and Thomas, 2011) and recognized that such perceptions relate to the formation of the PL brand image (Braak et al , 2014; Geyskens et al , 2010; Kumar et al , 2023; Steenkamp et al , 2010; Valaskova et al , 2018). Brand image refers to the perceptions and associations (Aaker, 1996; Anselmsson et al , 2007; French and Smith, 2013; Keller, 1993) “formed in the mind of a member of the external audience about the brand after one real or mental encounter with the brand”, and the accumulation of brand images constructs brand reputation, “an aggregate and compressed set of public judgments about the brand” (Veloutsou and Delgado-Ballester, 2018, p. 257) over time.…”
Section: Introductionmentioning
confidence: 99%
“…While in the field of technology, Apple Watch collaborates with Nike which notably expands the customer segment of the Apple Watch into sport-enthusiast consumers. In the same way, HnM, as a fast-fashion company, has collaborated with luxury brand designers which expand the product into luxury yet limited edition (Böger, Kottemann, & Decker, 2018). The application of different brand sectors has been applied between Reebok (sports outfits) and Pepsi (soft drinks) to do joint sales promotion which no combined product exists (Helmig et al, 2008).…”
Section: Literature Review 21 Co-branding: An Overview and Proposedmentioning
confidence: 99%